Perceived Vulnerability and Climate Change Impacts on Small-Scale Fisheries in Davao Gulf, Philippines - Macusi, Edison D.; Camaso, Kezia L.; Barboza, Anna; Macusi, Erna S. (Frontiers in Marine Science, 2021)
The small-scale fisheries play a critical role in food security and income of coastal fishing communities. However, climate variability and its impacts are affecting fishers, their communities, and fishing grounds. This study aimed to determine the perceived impacts of climate change and vulnerability of small-scale fisheries in selected fishing communities around the Davao Gulf. A semi-structured questionnaire was used to gather data on the perceptions of fishers (N = 220) on the impacts of climate change on their livelihood and communities. Seven focus groups corroborated the collected data and conclusions reached (N = 15). Principal component analysis (PCA) was used to reduce the sources of vulnerability and number of impacts of climate change. Regression was used to determine factors influencing the catch per unit effort (CPUE). The PCA results showed that for the vulnerability, the sources, coral bleaching, inadequate food, lack of credit access, changes in weather pattern and hotter temperature contributed highly. For the climate change impacts, the factors, less seasonality, unclear reproductive patterns, diseases in the catch, invasive species, decrease in catch and venturing farther to fish offshore were substantially influential. Further analysis showed that disease and invasive species, decrease in fish catch, fishing farther offshore, and monthly income affected the CPUE of the fisheries. Recommendations for climate change vulnerability reduction based on the conclusions reached in this study include more financial credit access, apprehension of illegal fishers, increased capacity building and technical skills for coastal communities, supplemental livelihoods, and information dissemination on climate change adaptation strategies.